1975
DOI: 10.1159/000178699
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Minimal Dosage of Melatonin Required to Inhibit Pineal Antigonadotrophic Activity in Male Golden Hamsters

Abstract: Blinding adult male golden hamsters was followed by atrophy, within 12 weeks, of the testes and accessory sex organs (seminal vesicles and coagulating glands) and by a significant reduction in pituitary prolactin levels. In experiment 1 blind hamsters received subcutaneously implanted melatonin-beeswax (1:24 mg) pellets at the following intervals: once per week, per 2, 3, 4, 6 weeks, or only one pellet during the 12-week experimental period. The melatonin-beeswax pellets, regardless of the frequency of implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

1976
1976
1997
1997

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…This is consistent with findings in hamsters where subcutaneous implants of mela tonin also prevent gonadal regression induced by light de privation [14], It is interesting to note that, in rats, dual sensory de privation is required to demonstrate the maximal anti gonadotrophic effects of the pineal gland while light de privation or merely exposure to short photoperiods pro duces the same effects in the hamster [15], In both species, pinealectomy totally reverses the antigonadotrophic effects on reproductive function. The pineal hormone melatonin was believed to account for the ability of the pineal to sup press reproductive physiology; yet, when administered continually (such as in the present study) it obviously acted as a counter antigonadotrophic agent.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with findings in hamsters where subcutaneous implants of mela tonin also prevent gonadal regression induced by light de privation [14], It is interesting to note that, in rats, dual sensory de privation is required to demonstrate the maximal anti gonadotrophic effects of the pineal gland while light de privation or merely exposure to short photoperiods pro duces the same effects in the hamster [15], In both species, pinealectomy totally reverses the antigonadotrophic effects on reproductive function. The pineal hormone melatonin was believed to account for the ability of the pineal to sup press reproductive physiology; yet, when administered continually (such as in the present study) it obviously acted as a counter antigonadotrophic agent.…”
Section: Discussionsupporting
confidence: 87%
“…The concept of melatonin being solely anti gonadotrophic in nature has recently been challenged by the discovery that chronic implantation of melatonin pel lets can actually prevent regression of the testes and the accessory sex organs induced by artificially shortened pho toperiods [15], by natural photoperiods during winter months [17], or by daily injection of melatonin [16]. The minimal effective dose of melatonin required to reverse the effects of light deprivation have been studied in male hamsters [14]. The purpose of the present study was to…”
mentioning
confidence: 99%
“…With respect to the lack of a graded response of accesso ry organ weights to different a.m. doses of melatonin, the only other dose-response study on the counterantigonado tropic effects of melatonin in male hamsters was conducted by Reiter et al [23]. They examined the influence of varying the amounts of melatonin in beeswax implants and the fre quency of implants on the reproductive system of blinded hamsters and found that both the testes and accessory or gans responded in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are similar to those observed in animals maintained in short days. On the other hand, administration of MT as a subcu taneous depot prevents short daily photoperiods from producing gonadal regression [17], Daily infusions of mela tonin for 12 h in the Djungarian hamster will produce go nadal regression while shorter infusions are progonadal [5,6]. Indeed MT can produce either progonadotropic or antigonadotropic effects [ 18] depending upon conditions of the experiment.…”
mentioning
confidence: 99%